UV-Induced Nanoparticles-Formation, Properties and Their Potential Role in Origin of Life - Nejdl, Lukáš; Zemánková, Kristýna; Havlíková, Martina; Burešová, Michaela; Hynek, David; Xhaxhiu, Kledi; Mravec, Filip; Matoušková, Martina; Adam, Vojtěch; Ferus, Martin; Kapuš, Jakub; Vaculovičová, Markéta (MDPI, 2020)
Inorganic nanoparticles might have played a vital role in the transition from inorganic chemistry to self-sustaining living systems. Such transition may have been triggered or controlled by processes requiring not only versatile catalysts but also suitable reaction surfaces. Here, experimental results showing that multicolor quantum dots might have been able to participate as catalysts in several specific and nonspecific reactions, relevant to the prebiotic chemistry are demonstrated. A very fast and easy UV-induced formation of ZnCd quantum dots (QDs) with a quantum yield of up to 47% was shown to occur 5 min after UV exposure of the solution containing Zn(II) and Cd(II) in the presence of a thiol capping agent. In addition to QDs formation, xanthine activity was observed in the solution. The role of solar radiation to induce ZnCd QDs formation was replicated during a stratospheric balloon flight.

Inorganic nanoparticles might have played a vital role in the transition from inorganic chemistry to self-sustaining living systems. Such transition may have been triggered or controlled by processes requiring not only versatile catalysts but also suitable reaction surfaces. Here, experimental results showing that multicolor quantum dots might have been able to participate as catalysts in several specific and nonspecific reactions, relevant to the prebiotic chemistry are demonstrated. A very fast and easy UV-induced formation of ZnCd quantum dots (QDs) with a quantum yield of up to 47% was shown to occur 5 min after UV exposure of the solution containing Zn(II) and Cd(II) in the presence of a thiol capping agent. In addition to QDs formation, xanthine activity was observed in the solution. The role of solar radiation to induce ZnCd QDs formation was replicated during a stratospheric balloon flight.
UV-Induced Nanoparticles-Formation, Properties and Their Potential Role in Origin of Life
Keywords: UV-induced nanoparticles; origin of life; metal ions; thiols; nanoparticle-based world; nanozymes; UV-induced nanoparticles; origin of life; metal ions; thiols; nanoparticle-based world; nanozymes